The Prospects and Promises of “Interglaciations” - Morgan, Alan (Géographie physique et Quaternaire, 1990)
ABSTRACTThe term "interglacial" has been subject to numerous changes since its inception. This essay provides a brief historical summary, and suggests that the assignation of "interglacial" status to terrestrial deposits should be reviewed. Past, and the present, interglaciations are particularly important in analysing earlier periods of global change. Proxy-data records of these intervals can provide valuable parameters which should be utilised by modellers to help man-kind face the results of anthropogenic modifications of the environment.